Influence of green investment, institutional ownership and environmental performance on company value with profitability as a mediation variable: A Study on energy sector listed on Indonesia stock exchange 2019 –2023 - Sukmana, Asep Heri; Suzan, Leny (Edelweiss Applied Science and Technology, 2025)
This study aims to analyze the impact of green investment, institutional ownership, and environmental performance on firm value, with profitability as a mediating variable in energy sector companies listed on the IDX between 2019 and 2023. Firm value reflects investors’ perceptions of a company’s future prospects, where sustainability practices are increasingly considered strategic in investment decisions. Using secondary data from the annual and sustainability reports of energy sector corporations, this study employs a quantitative method. Panel data methodologies were used for analysis, and the research design is cross-sectional. The results indicate that institutional ownership, environmental performance, and green investment all significantly affect corporate value. While environmental performance has no direct effect on firm value, green investment and institutional ownership both have a positive and substantial impact. It has been established that profitability mediates the relationship between institutional ownership and firm value, as well as green investment, but it does not mediate the relationship between environmental performance and firm value. These findings highlight the importance of financial success in strengthening the strategic impact of sustainability activities on company value in the energy industry.